ASPEK-ASPEK PERENCANAAN STRATEGIK PENDIDIKAN - Mustika Sariah Siagian; Zamsiswaya (STKIP Subang, 2026)
Strategic planning is a crucial foundation for maintaining the sustainability, relevance, and competitive advantage of educational institutions amidst the rapid dynamics of global change. This article aims to analyze seven fundamental aspects of strategic educational planning: self-evaluation, formulation of vision, mission, and objectives, identification of strategic issues, development of strategic programs, and determination of targets and achievement strategies. This study uses a qualitative approach with a literature review method. Data were obtained from books, articles, and documents relevant to the field of educational management and strategic planning. The findings indicate that the effectiveness of strategic planning depends not only on the completeness of administrative documents but also on the alignment between the institution's internal conditions and the external challenges faced. This analysis emphasizes the importance of leadership commitment and the active participation of all stakeholders in translating strategic plans into concrete actions. The results of the study indicate that strategic planning can be a foundation for developing directed, adaptive, and sustainable educational management. Through the implementation of integrated strategic planning, educational institutions can improve the effectiveness of organizational management and strengthen competitiveness in facing various challenges and changes in the educational environment.